The gut microbiota intervenes in glucose tolerance and inflammation by regulating the biosynthesis of taurodeoxycholic acid and carnosine - Zhen, Jianhua; Zhang, Yunan; Li, Yini; Zhou, Yali; Cai, Yanan; Huang, Guangrui; Xu, Anlong (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveThis study aims to investigate the pathogenesis of hyperglycemia and its associated vasculopathy using multiomics analyses in diabetes and impaired glucose tolerance, and validate the mechanism using the cell experiments.MethodsIn this study, we conducted a comprehensive analysis of the metagenomic sequencing data of diabetes to explore the key genera related to its occurrence. Subsequently, participants diagnosed with impaired glucose tolerance (IGT), and healthy subjects, were recruited for fecal and blood sample collection. The dysbiosis of the gut microbiota (GM) and its associated metabolites were analyzed using 16S rDNA sequencing and liquid chromatograph mass spectrometry, respectively. The regulation of gene and protein expression was evaluated through mRNA sequencing and data-independent acquisition technology, respectively. The specific mechanism by which GM dysbiosis affects hyperglycemia and its related vasculopathy was investigated using real-time qPCR, Western blotting, and enzyme-linked immunosorbent assay techniques in HepG2 cells and neutrophils.ResultsBased on the published data, the key alterable genera in the GM associated with diabetes were identified as Blautia, Lactobacillus, Bacteroides, Prevotella, Faecalibacterium, Bifidobacterium, Ruminococcus, Clostridium, and Lachnoclostridium. The related metabolic pathways were identified as cholate degradation and L-histidine biosynthesis. Noteworthy, Blautia and Faecalibacterium displayed similar alterations in patients with IGT compared to those observed in patients with diabetes, and the GM metabolites, tauroursodeoxycholic acid (TUDCA) and carnosine (CARN, a downstream metabolite of histidine and alanine) were both found to be decreased, which in turn regulated the expression of proteins in plasma and mRNAs in neutrophils. Subsequent experiments focused on insulin-like growth factor-binding protein 3 and interleukin-6 due to their impact on blood glucose regulation and associated vascular inflammation. Both proteins were found to be suppressed by TUDCA and CARN in HepG2 cells and neutrophils.ConclusionDysbiosis of the GM occurred throughout the entire progression from IGT to diabetes, characterized by an increase in Blautia and a decrease in Faecalibacterium, leading to reduced levels of TUDCA and CARN, which alleviated their inhibition on the expression of insulin-like growth factor-binding protein 3 and interleukin-6, contributing to the development of hyperglycemia and associated vasculopathy.